APPLICATION OF DATA IN THE CENTRE LIBRARY UNIVERSITY - Marzuki Marzuki (JAKSTIK Journal, 2006)
Data center or data center is the facility used to put multiple servers or computer systems and data storage systems (storage) are conditioned by setting catudaya and air, fire protection, and are usually equipped also with physical security systems. Data centers can also be viewed as a repository of data (data warehouse) which serves as a data management system starting from the collection, processing, storage until the rediscovery of the data, and be able to also provide support in decision-making (decisionsupport system). Library Center may implement a data center (called CITED Data Center, PDC) to manage numerous databases, ie databases, books, magazines, multimedia, and publications. PDC consists of: (1) Back-end, to manage information; (2) PDC or network attached storage (NAS), a large-capacity storage media to store digital documents, and (3) front-end, as the medium of communication between systems PDC and users. Implementation should be supported PDC network infrastructure, IT equipment, applications, standard operating procedures, and managing resources, both in quantity and capability.